Ženski bijeg iz domovine / A Woman's Escape from the Homeland - Gazetić, Edisa (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Exile is one of the most popular topics in the 20th, but also in the 21st century, when non-democratic societies persecute individuals because of their resistance to repressive regimes around the world. Because of their activism many individuals are labeled as enemies of such political systems, and many of them are punished in various ways by the system they fighting against. This paper attempts to present some examples of female authors around the world who had to leave their homeland and go into exile for opposing regimes. These systems are always connected with the patriarchal ideology, then this struggle is even harder for women.